LIFE-THREATENING HEMORRHAGE FROM POSTOPERATIVE NECK WOUND- A CASE REPORT - Proletina Bozdukova (Science & Research)

(untitled)
Oral cavity carcinoma is a malignant disease that accounts for 30% of all head and neck carcinomas. It occurs about 4 times more often in men than in women. Predisposing factors include tobacco smoking, regular alcohol consumption, poor oral hygiene, chronic dental diseases, and HPV (Human Papillomavirus) infection. The rich blood supply to the head and neck is a cause for the frequent and early metastasis to regional lymph nodes in malignant diseases with primary localization in the structures of the oral cavity. In this report, we present a clinical case of a 51 year old man with carcinoma of the floor of the oral cavity with metastases to the submandibular lymph nodes - level IB, who underwent surgical treatment with adjuvant radiotherapy for the primary tumour and neck metastases at another medical institution. He was admitted to ENT Clinic-UMHAT Burgas urgently due to bleeding from an open postoperative wound measuring approximately 5 cm in diameter in the submandibular region. Multiple blood transfusions were performed due to low hemoglobin levels (52g/L). After stabilizing the patient, several surgical interventions were performed in stages to close the postoperative wound, initially covered with a deltopectoral flap. Subsequent surgical interventions included selective lymph node dissection and flap remodelling. After completing the surgical treatment, repeat radiotherapy was performed in the neck area with a volume of 60 Gy, followed by a control fluorodeoxyglucose-positron emission tomography (FDG-PET), which revealed an active lymph node from the upper jugular group suspicious for metastasis. A core biopsy of the lesion was performed, histologically confirming the diagnosis. An operative intervention was undertaken to remove the jugular lymph nodes and cover the surgical wound with a supraclavicular flap.